1989
DOI: 10.1016/0304-3959(89)90044-4
|View full text |Cite
|
Sign up to set email alerts
|

EMLA cream in the treatment of post-herpetic neuralgia. Efficacy and pharmacokinetic profile

Abstract: The analgesic efficacy of 5% of EMLA cream (5 or 10 g) when applied for 24 h periods was evaluated in 5 female and 7 male patients (mean age 69 years, range 50-85 years) with refractory post-herpetic neuralgia (PHN). Mean visual analogue pain intensity scores for all patients were significantly improved 6 h after application (P less than 0.05). In a subgroup of patients with facial PHN receiving EMLA cream, 5 g (n = 4), there were significant improvements in pain intensity scores at 6 h (P less than 0.05). 8 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 13 publications
0
30
0
1
Order By: Relevance
“…Such formulations are widely used as topical anesthetics for minor acute surgical procedures (Lener et al, 1997), and there are some reports of use in chronic pain conditions such as postherpetic neuralgia (Stow et al, 1989;; but see Devers and Galer, 2000). Clinical attention has focused recently on topical formulations of lidocaine.…”
Section: Local Anestheticsmentioning
confidence: 99%
“…Such formulations are widely used as topical anesthetics for minor acute surgical procedures (Lener et al, 1997), and there are some reports of use in chronic pain conditions such as postherpetic neuralgia (Stow et al, 1989;; but see Devers and Galer, 2000). Clinical attention has focused recently on topical formulations of lidocaine.…”
Section: Local Anestheticsmentioning
confidence: 99%
“…19 Oral steroids may add to the benefit of anti-viral therapy for reducing the pain of AHZ but have no effect on the development of PHN. 3 A lidocaine patch 20 and EMLA cream 21 may help in PHN and AHZ. Oral oxycodone, meperidine and methadone all have NMDA-antagonist effects and may treat the acute pain better than other narcotics that do not.…”
Section: Cas No 1 : Une Femme De 79 Ans Porteuse D'une Valvule Mitramentioning
confidence: 99%
“…[38][39][40][41][42][43] In a randomized, placebo-controlled, single-blind study of iontophoresis of vincristine, only minimal benefit was found and all subjects reported burning at electrode sites (class II). 44 Reports of benefit from topical application of lidocaine gel, 45 topical lignocaine/prilocaine cream, 46 intralesional injections of triamcinolone, [47][48][49] and cryocautery with dry ice 50 were limited to class IV studies. Conclusion.…”
Section: R E T I R E D R E T I R E Dmentioning
confidence: 99%